(untitled) - Dr. M. Mary Jansirani, K.Jamshida (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper presents Runge-Kutta (RK) method based on Arithmetic Mean (AM), Geometric Mean (GM), Harmonic Mean (HaM), Heronian Mean (HeM), Root Mean Square (RM), Centroidal Mean (CeM) and Contraharmonic Mean (CoM) to solve the intuitionistic Fuzzy differential equations (IFDEs). The efficiency of these methods has been illustrated through numerical examples of intuitionistic fuzzy differential equations